EVALUATION OF THE OCCLUSION WITH TWO DIFFERENT METHODS: A T-SCAN II OCCLUSAL ANALYSIS AND THE TEETHAN SYNCHROMYOGRAPHY RECORDING SYSTEM - Vladimir Bogdanov; Ivan Chakalov (Journal of IMAB)
The article presents a case of a sixty-seven-year-old female patient who complains of an uncomfortable bite after full-mouth rehabilitation three months ago. Before inserting the crowns, the patient did not have any complaints. The complaints included: chewing only unilaterally (on the right side), and premature contact in the left canine area. Also the patient suffered masticatory muscles soreness in the afternoons and uncomfortable bite that started after the rehabilitation with zirconium crowns. Evaluation of the occlusal contacts is necessary after any dental intervention which affects occlusion. In this case report, two methods for evaluation of the occlusion are compared – one with a T-scan analysis, using a sensor between the teeth, and the second by evaluating the electromyographic activity of the masticatory muscles (via surface electromyography (sEMG). The occlusion was estimated by both methods during voluntary clenching, and the results from both methods were compared. Articulating paper was used for visualization of the contacts as an additional method. Conclusion: The results of the two methods (T-scan analysis and through sEMG) were very similar. In this clinical case, the application of both the T-Scan II occlusal analysis and the Teethan sEMG system demonstrated their effectiveness in evaluating and improving occlusal balance and muscle activity following extensive dental rehabilitation. The complementary nature of these diagnostic methods was highlighted, with each providing distinct and valuable insights—T-Scan focusing on the occlusal force and timing, while Teethan emphasized neuromuscular balance. The occlusal adjustments informed by these technologies significantly alleviated the patient's discomfort, confirming their utility in clinical practice for diagnosing and addressing occlusal discrepancies. This case reinforces the importance of integrating advanced diagnostic tools to ensure optimal patient outcomes in prosthetic and restorative dentistry.